THE CARTESIAN THINKING SUBJECT: THE PROBLEM OF THE NONGNOSEOLOGICAL DIMENSION - Nerijus Milerius (Problemos)
The article deals with the problem of the nongnoseological dimension of the Cartesian subject. The Cartesian theory of subject has centered around the gnoseological discourse of philosophy of the New Ages. On the other hand, namely due to this reason, the crisis of the gnoseological discourse has made clear the indispensable contradictions of the Cartesian subject theory itself. According to the author, the only possibility to discuss the problem of the nongnoseological dimension of the Cartesian subject is to analyze the procedures by means of which the thinking I transforms itself into an acting and knowing subject. Analysis of these procedures, however, have revealed their uniqueness and indefiniteness. Thus, the definition of the nongnoseological dimension of the Cartesian subject does not seem to be possible.